Evaluation of the potentials of Bacillus subtilis KM16 and Pseudomonas sp. PAP 26 isolated from the hot spring and crater lakes as antibiofilm agents - Stella Magdalena; Fabiola Giovani; Yogiara Yogiara (International Journal of Applied Biology, 2021)
Bacteria can interact with each or other microorganisms by releasing, sensing, and reacting to small diffusible chemical signal molecules to alter their community behavior. This process, termed quorum sensing, is influenced by density of other bacteria that present in the environment. One example as a result of this process is the formation of biofilm. Biofilm consists of bacterial communities that attach to a surface and envelope themselves in secreted polymers. This formation can be beneficial to pathogenic bacteria because they become highly resistant to antibiotics and human immunity. Thus, antibiofilm agents that can inhibit biofilm formation are needed. The objective of this study were to screen and evaluate bacteria from hot spring and crater lakes that have antibiofilm activity against pathogenic bacteria. In this study, 26 isolates were successfully obtained and tested for quorum sensing and quorum quenching activities. Based on the result, two isolates, which were KM16 and PAP26, were found to have quorum quenching activity. Further research showed that KM16 and PAP26 had antibiofilm activity against more than six pathogenic bacteria. From characterization of the bioactive compounds, it is known that different compound from KM16 and PAP26 have different activity against each pathogen. In molecular identification, isolates KM16 and PAP26 were identified as Bacillus subtilis and Pseudomonas sp. through molecular identification.